Karakteristik Fisikokimia “Liang Teh Pontianak (LTP)” Rasa Sari Apel dengan Pemanis Stevia (Stevia rebaudiana) - Rafika Suci; Yohana Sutiknyawati Kusuma Dewi; Maherawati Maherawati (Jurnal Penelitian Pertanian Terapan, 2025)
Liang Tea Pontianak (LTP) is a functional drink made from several herbal leaves and sucrose as a sweetener. Sucrose has a sufficiently high calorie content that a reduction in sucrose consumption is necessary. Sweetener stevia is a natural sweetener that is sweeter and lower in calories, but the stevia it contains gives the aftertase a slightly bitter taste. Apples have medium sweet and sour properties so that they can be used to add to the taste of liang tea drinks. The purpose of this study was to obtain the ratio of stevia and sucrose in the formulation of LTP apple cider flavor based on physicochemical and sensory characteristics. The design used in this study is a randomized Group Design (RAK) which consists of one factor, namely the comparison of sucrose and Stevia Sweetener (s) with 3 replications and 21 treatment units. The comparison of sucrose and stevia sweeteners is 100%:0%, 99.82%:0.18%, 99.63%:0.37%, 99.44%:0.56%, 99.23%:0.77%, 99.01%:0.99% and 98.78%:1.22%. The data obtained will be analyzed statistically by using analysis of variance. When the data show siqnificant differences, then using BNJ with the real level 5%. Liang tea apple flavor with sucrose sweetener ratio: stevia (99.01:0.99) % has the best physicochemical and sensory properties of total Acid 3.40%, antioxidant activity 49.86%, reducing sugar 14.50%, *L value 26, 83, *a of 1.90 and b* 4.30 with sensory characteristics of color 4.30 (like), aroma 3.83 (like), taste 4.1 (like) and overall preference 4.06 (like), taste 4.1 (like) and overall liking 4.06 (like).